Viabilidade de utilização de técnicas de agricultura de precisão na lavoura orizícola - Mainardi, Leonardo Cezar (2015)
Rice cultivation is on fundamental importance to the state s economy, where there is a need for improvements in productivity and profitability of farming located. This paper aimed to evaluate the production costs of the implementation of a rice farming using techniques of Precision Agriculture to obtain better productive incomes. The experiment was performed in the city of Rosário do Sul RS, in constant cultivation and with rotation of the rice, soy and grazing crops. The studied area is a section of 55 hectares and the methodology implemented was the comparative of two consecutive years of irrigated rice cultivation, being the crop in a conventional fertilization system in 2012/2013 and in 2013/2014 the cultivation was with the implementation of Precision Agriculture techniques. Necessary tools for the soil geo-referenced sampling were used to implement the Precision Agriculture techniques, and the recommendation and elaboration of input application maps. Through the obtained analysis, recommended corrections were made with the application of chalk, potassium and phosphorus in a variable rate, for goals of high crop efficiency. The result of the experiment determined a production cost for the implementation of precision agriculture techniques of 30,20% higher than the conventional crop cost. Respectively, it was also obtained an efficiency of 14,30% higher and profitability of 10,85% higher than the conventional crop. The reevaluation of the soil after the crop of 2013/2014 showed a significant improvement on the chemical attributes of the soil, justifying the high initial investment of the techniques implementation. Besides, the economic viability to purchase the centrifugal destributor was analyzed. This acquisition seemed to be economically viable for areas bigger than 200 hectares, if compared to the cost of service provider companies.